A New Era in Taiwan Politics and its Implications. (2nd January 2017) - Tan, Andrew T. H.
Abstract : Taiwan faces an uncertain future after the electoral victory of the pro-independence Democratic Progressive Party (DPP) in the January 2016 elections. The election results, which reflected growing pro-independence sentiments amongst a younger generation of Taiwanese, have set Taiwan on a collision course with China, which is increasingly impatient for reunification to occur. The new US president, Donald Trump, has also added to the tensions by openly questioning the "One China" policy. Another Taiwan Strait crisis today would be fraught with immense risks due to China's dramatic economic and military rise which has altered the regional power balance. Given the increasingly tense China-US strategic rivalry, the US is also not likely to sit idly by should China attack Taiwan. However, the key player in resolving the Taiwan problem is China. For various reasons, it is in fact in China's interest to be patient with the current situation, and maintain the status quo for the immediate and medium-term future, while it constructs a new strategy that could win over the people of Taiwan, since true reunification can only occur if the people on Taiwan willingly accept it.